Sustainable Supply Chain Management - Morana, Jo?lle. (Wiley-ISTE, 2013)
It is commonly recognized that logistics has become a major strategic issue for all companies, whether they are part of the primary, secondary or tertiary sector. Faced with the external pressures of globalization and competition, logistics optimizes processes and reduces production and delivery cycles. The use of Sustainable Supply Chain Management (SuSCM) is now increasingly at the center of thought, due to the numerous factors favoring its implementation: requests from various stakeholders, governmental pressures (decrees, laws, regulations, etc.), environmental pressures (pollution.
4.3. The dashboards currently used in logistics4.4. The indicators used in Sustainable SupplyChain Management Balanced Scorecard; 4.5. Conclusion; General conclusion; Bibliography; Acronyms and Abbreviations; Index.
Includes bibliographical references and index.
Print version record.
Keywords: Business logistics; BUSINESS & ECONOMICS -- Production & Operations Management; TECHNOLOGY & ENGINEERING -- Industrial Engineering; TECHNOLOGY & ENGINEERING -- Industrial Technology; Business logistics; Electronic books